A Mass Mediated Interpretation of the Chinese “Belt & Road Initiative” as Strategic Intelligence Perspective - Schnell, James A.; Schnell, Brian L. (European Journal of Applied Sciences, 2017)
This paper contrasts the current Chinese “Belt and Road Initiative” (BRI) against the opening of the U.S. west in the 19th century using principles of western rhetoric as basis for interpretation. Most specifically, Kenneth Burke’s Dramatistic Pentad is used for initial clarification along with explanation of how further understanding can be realized via Fantasy Theme Analysis to better appreciate the expression of rhetorical vision. Recognition of how BRI can be understood differently, depending on the cultural context, is stressed as a strategic intelligence perspective. This is couched in the contextual framing of mass media influences as explained by Marshall McLuhan.